Evaluación y comportamiento de rei2fol como nueva estrategia en el control de sigatoka negra mycosphaerella fijiensis morelet - Zapata Seberino, Douglas Wilfrido (2013)
On the farm Santa Ines of the Technical University of Machala, a test was impleme investigate the behavior of Rei2fol evaluation and, as a new strategy for control of black sigatoka. The objectives were: 1) Establish the effect potentiator Rei2fol over other conventional products for the control of black sigatoka (Mycosphaerella fijiensis M.) 2) Compare the cost of Rei2fol through economic analysis, with the treatments used for the management of black sigatoka. The treatments investigated were: T1 Impulse + Cumora (0.4 +0.4 l / ha); T2 Rei2fol + Cumora (0.4 +0.5 l / ha); T3 Impulse + Bumper (0.4 +0.4 l / ha); T4 Rei2fol + Bumper (0.4 +0.5 l / ha); T5 Impulse + Dithane (1.75 +0.4 l / ha) and T6Rei2fol + Dithane (1.75 + 0.4 l / ha). Plots were established design arranged in arandomized block field, treatments consisted of a single dose of the product, applied in the experimental plots, when the degree of infection reached a level that was determined by the method of biological warning. The variables evaluated were: Folia emission rate (REF), Infection third leaf, fourth leaf Infection, Infection in fifth leaf, gross amount (SB), evolutionary stage of the disease (EE). All variables was obtained high statistical significance. 1) Control of systemic disease and other chemical protectants, belonging to the chemical group of the triazoles, spiroxaminas, mixed amines Rei2fol if interfered with, reducing the development of the pathogen. 2) which was used treatments Rei2fol mixed with a chemical fungicide, was able to obtain a minor infection, compared to the treatments with fungicides used two, giving an alternative to the banana industry to control black sigatoka, costs and impact menorando environment. 3) The analysis of variance showed Duncan's test treatment had no effect on the index of leaf.